A CASE OF LATE DIAGNOSIS OF FAMILIAL MEDITERRANEAN FEVER COMPLICATED BY AA-AMYLOIDOSIS - S. I. Shchadneva; E. E. Ustinova; L. V. Belozertseva; V. V. Gorbunov; N. S. Kurbatova (Klinicist)
The aim of study was to describe a clinical case of a hereditary disease with autosomal recessive type of inheritance – familial Mediterranean fever (FMF).Materials and methods. Patient A., 19 years old, Armenian, was hospitalized in the Department of rheumatology of the clinical hospital with complaints of periodic temperature rises to 39 °C, paroxysmal pain in the abdomen, ankle and hip joints, legs edema. In anamnesis from 8 months of age there were attacks of 1–2 day abdominal pain in combination with febrile fever; from 2 years there were arthralgia of the ankle joints, followed by knee and hip. Attacks of fever and joint syndrome recurred 3–4 times a year, lasted for 2–3 days, and disappeared spontaneously. Treatment with nonsteroidal anti-inflammatory drugs and small doses of prednisone was carried out. The examination in the hospital revealed nephrotic syndrome without impaired renal function, increasing of erythrocyte sedimentation rate (up to 62 mm/h), C-reactive protein (up to 60 mg/dl), leukocytosis (up to 16.7 × 109/L). The immunological examination revealed no abnormalities. Bacteriological and serological studies have ruled out the possibility of infectious diseases. Electrocardiography, echocardiography, ultrasound of abdomen and kidneys, multispiral computed tomography of kidneys and retroperitoneum, magnetic resonance imaging of the sacroiliac joints, nephrobiopsy were performed.Results. During the examination, a wide differential diagnosis with infectious and rheumatic diseases was carried out. Taking into account the polysyndromicity of clinical manifestations, systemic lupus erythematosus was suggested. An induction course of immunosuppressive therapy was conducted, that was ineffective. The diagnosis of systemic lupus erythematosus was doubtful and to clarify the nature of kidney morphological changes nephrobiopsy was performed that revealed the presence of kidneys AA-amyloidosis. Given these data in conjunction with clinical manifestations, the patient»s nationality, FMF was diagnosed and colchicine 2 mg/day was appointed. It was possible to stop the clinical symptoms of inflammation in FMF, but the nephrotic syndrome due to amyloidosis persists.Conclusion. The presented observation demonstrates the complexity of FMF diagnosis that verified 18 years after the appearance of the first disease symptoms. The diagnosis was helped by the presence of disease clinical manifestations and kidneys morphological study that revealed the development of a serious complication of periodic disease – AA-amyloidosis. Treatment with colchicine allowed to stop the symptoms of periodic disease.